Werner Syndrome Caused by Homozygous Frameshift Variant c.1578del in WRN - Druta, Jovita Patricija; Petraitytė, Gunda; Sasnauskienė, Aušra; Preikšaitienė, Eglė (Acta medica Lituanica, 2024)
Background. Progerias are rare hereditary genetic disorders that cause the onset of aging to occur earlier than generally expected, which initiates the progression of many age-related diseases. Syndromes assigned to this group are usually a compound disturbance of multiple systems. Werner syndrome is among a few well described premature aging disorders associated with a higher likelihood of malignancies. Clinical case. We present a 45-year-old man with a history of painful muscle spasms, general muscle pain and weakness. There was a progression of contractures of the plantar tendons, as well as the atrophy of the subcutaneous adipose tissue of the extremities. The patient was initially diagnosed with secondary small fiber sensory polyneuropathy and myotonia, but further genetic testing revealed the homozygous pathogenic variant c.1578del in the WRN gene associated with Werner syndrome. Conclusions. The c.1578del variant, previously not described in literature in a homozygous state, causes Werner syndrome and is associated with the pronounced hallmarks of early senescence in the proband’s fibroblasts. Molecular diagnosis brings better treatment of manifestations and monitoring options for the patients, helping to establish more sufficient and secure patient care.